2018
DOI: 10.1186/s12935-018-0682-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of TGFBR1, TLR4 are associated with prognosis of gastric cancer in a Chinese population

Abstract: BackgroundHelicobacter pylori (H. pylori)-induced gastric cancer is an intricate progression of immune response against H. pylori infection. IL-16, TGF-β1 and TLR4 pathways were the mediators involved in the immune response. We hypothesized that genetic variations in genes of these pathways have potential susceptibility to gastric cancer risk, and predict clinical outcomes of patients.MethodsTo investigate the susceptibility and prognostic value of genetic variations of IL-16, TGFBR1 and TLR4 pathways to gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
1
19
1
3
Order By: Relevance
“…Sepahi et al found that rs334348 functional variants were associated with endometriosis severity . Additionally, no association between rs334348 polymorphism and clinical outcomes of gastric cancer patients was also reported . The present prospective study with large‐scale sample size suggested a significantly and independently association between rs334348 polymorphism and the better DSS of oral cancer.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Sepahi et al found that rs334348 functional variants were associated with endometriosis severity . Additionally, no association between rs334348 polymorphism and clinical outcomes of gastric cancer patients was also reported . The present prospective study with large‐scale sample size suggested a significantly and independently association between rs334348 polymorphism and the better DSS of oral cancer.…”
Section: Discussioncontrasting
confidence: 49%
“…This pathway is vital in the development and progression of malignancy by regulating cellular proliferation and differentiation . Previous researches have shown that genetic polymorphism and aberrant expression of TGFBR1 were associated with prognosis of several digestive tract cancers, including gastric cancer and colorectal cancer . Additionally, a recent study also demonstrated that higher TGFBR1 expression may represent poor prognosis in advanced head and neck squamous cell carcinomas (HNSCC) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that TGF-β1 expression is increased in prostate cancer ( 46 ), ovarian cancer ( 47 ), hepatocellular carcinoma ( 12 ), bladder cancer ( 48 ), breast cancer ( 49 ) and cholangiocarcinoma ( 50 ), suggesting that abnormal TGF-β1 expression can influence tumor invasiveness and result in a poor prognosis. Regarding TGF-βR1, a previous study has found that it promotes tumor angiogenesis by upregulating matrix metalloproteinase 9 in metastatic human melanoma cells ( 51 ) Moreover, changes in TGF-βR have been observed in numerous types of human tumors, such as breast ( 52 , 53 ), colon ( 54 ) and gastric cancer ( 20 ), and are characterized by gene mutations, decreased levels or inactivation of TGF-βR. TGF-βR1 mutations have been reported in malignant tumors of the ovary, breast and pancreas, as well as in colon cancer ( 16 , 52 - 56 ).…”
Section: Tgf-β Tgf-βr1 and Malignant Tumorsmentioning
confidence: 99%
“…Mutant cells that lack TGF-βR1 do not respond to TGF-β1, which further affects the transduction of the TGF-β signaling pathway ( 16 , 17 ). Additionally, the activation or overexpression of TGF-βR1 is observed in different types of tumor and can serve an important role in tumor cell proliferation and migration to other tissues by taking part in EMT ( 18 ), such as in colon ( 19 ) and gastric cancer ( 20 ). Previous studies ( 20 - 22 ) have revealed that TGF-βR1 is observed in different types of tumor and serves an important role in tumor metastasis by participating in cancer development, cell migration and blood vessel regeneration, leading to unsatisfactory responses to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this aim, gene association studies are required as personalized information to predict the disease outcomes. Single nucleotide polymorphisms (SNPs) in the TLR4 gene were associated with both infectious diseases and non-communicable diseases [22][23][24]. To date, several positions of TLR4 polymorphisms have been examined for proposal as risk or protective factors of glaucoma.…”
Section: Introductionmentioning
confidence: 99%